The Role of Metarepresentation in the Production and Resolution of Referring Expressions - Horton, William S.; Brennan, Susan E. (Frontiers in Psychology, 2016)
In this paper we consider the potential role of metarepresentation—the representation of another representation, or as commonly considered within cognitive science, the mental representation of another individual’s knowledge and beliefs—in mediating definite reference and common ground in conversation. Using dialogues from a referential communication study in which speakers conversed in succession with two different addressees, we highlight ways in which interlocutors work together to successfully refer to objects and achieve shared conceptualizations. We briefly review accounts of how such shared conceptualizations could be represented in memory, from simple associations between label and referent, to "triple co-presence" representations that track interlocutors in an episode of referring, to more elaborate metarepresentations that invoke theory of mind, mutual knowledge, or a model of a conversational partner. We consider how some forms of metarepresentation, once created and activated, could account for definite reference in conversation by appealing to ordinary processes in memory. We conclude that any representations that capture information about others’ perspectives are likely to be relatively simple and subject to the same kinds of constraints on attention and memory that influence other kinds of cognitive representations.